Identifikasi Sikap Implikasi Sosial dari Fisika, Normalitas Ilmuwan, dan Adopsi Sikap Ilmiah - Ependi, Radias; Puspitasari, Tari Okta; Sandi Pratiwi, Nur Ika (Attractive : Innovative Education Journal, 2020)
The purpose of this study was to find out how the attitude of students of SMAN 8 Jambi City towards Physics subjects. This type of research is a quantitative study with a survey research design. Data collection techniques used a questionnaire or questionnaire and used a 5-point Likert scale. This research involved 174 students of SMAN 8 Kota Jambi. Data analysis in this study used descriptive statistics. Indicators used in this study are the Social Implications of Physics, Scientific Normality and Adoption of Scientific Attitudes. The analysis results obtained on indicators of the social implications of physics are good with 54.6% presentation. Indicator of attitude toward scientific normality is sufficient with 61.5% presentation, and indicator of scientific attitude adoption is good with presentation of 49.4%. Keywords: Attitude, Social Implications Of Physics, Scientific Normality, Adoption Of Scientific Attitudes.